Experimental pancreatic islet treansplantation - Gray, D; Gray, D. W. R. (1984)
﻿ Two major problems preventing the clinical application of pancreatic islet transplantation were investigated. The problem of allograft rejection was studied in rats, made diabetic by streptozotocin treatment. It was shown that DA rats given LEW renal allografts and treated with cyclosporine accepted their grafts, and subsequently developed a strain-specific unresponsive state that allowed successful transplantation of LEW islets without further immunosuppression, whilst BN islets were rejected normally. The effect was demonstrated to be independent of the site of islet transplantation, and, once an islet allograft had been accepted, it was possible to remove the original renal allograft without affecting the transplanted islets. The effect was shown to apply to another strain combination (LEW into PVG), and also to animals made unresponsive to renal allografts by another method (donor-specific blood transfusion). The problem of separation of adequate numbers of viable islets from the pancreas was studied in the rat, dog, pig and human. To aid the investigation, supravital staining techniques were developed, using neutral red to identify the islets, and fluorescein diacetate and ethidium bromide to assess islet viability. A variety of islet isolation techniques were investigated, and a new technique for isolation of islets from the dog pancreas, yielding up to 160,000 islets from 1 pancreas with a maximum purity of 80%, was developed. The structural integrity and in vitro function of the isolated islets was demonstrated, but it was not possible to prevent diabetes by autotransplantation of islets to the portal vein of pancreatectomised dogs. A method for isolation of islets from the human pancreas was developed from that used in the dog, yielding up to 80,000 islets from a whole pancreas, with a maximum purity of 40%. The technique was shown to be both simple and reliable. The structural integrity and in vitro function of the isolated islets was demonstrated, and the viability of the islets proven by successful transplantation under the kidney capsule of nude mice.